2014
DOI: 10.7314/apjcp.2014.15.2.687
|View full text |Cite
|
Sign up to set email alerts
|

Single Center Experience on Causes of Cancer Patients Visiting the Emergency Department in Southwest Turkey

Abstract: Background: Emergency departments are visited by cancer patients for palliation of cancer-related symptoms, management of treatment-related side effects, oncologic emergencies, co-morbidities, and/or end of life care. In this study, we aimed to identify the characteristics of cancer patients admitted to an emergency medicine department in Southwest Turkey. Materials and Methods: In this retrospective descriptive study, a total of 304 emergency department admissions of 102 patients with cancer due to medical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
0
12
1
Order By: Relevance
“…[16] In national studies, it has been reported that among all cancers, lung cancer was the most frequent ED admission reason and multiple lung metastases were the most common non-pulmonary metastatic malignancies. [17,18] In our series, bronchitis was the most common diagnosis among chest disease patients, while hospitalization was required in 4% of them and consultation from a chest disease specialist was required in lower than 1%. Besides, it was thought that some patients misused the emergency services.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…[16] In national studies, it has been reported that among all cancers, lung cancer was the most frequent ED admission reason and multiple lung metastases were the most common non-pulmonary metastatic malignancies. [17,18] In our series, bronchitis was the most common diagnosis among chest disease patients, while hospitalization was required in 4% of them and consultation from a chest disease specialist was required in lower than 1%. Besides, it was thought that some patients misused the emergency services.…”
Section: Discussionmentioning
confidence: 65%
“…Discharge rates from ED are reported as 81-88% in our country. [17,[21][22][23] Kekeç et al reported that 60% of the patients aged ≥65 years applying to ED of a university hospital in Adana, were hospitalized, and 5.1% of them werehospitalized in the chest diseases clinic. [16] In another study investigating elderly patients, 20% of the hospitalizations of ED admissions, were most frequently to the clinics of cardiology and chest diseases among clinics of internal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a significant reduction in inpatient admission rate was observed from 2014 to 2015 which is likely due to the proper management of cancer patients with avoidance of unnecessary hospitalizations. Furthermore, the specialistoriented treatment of these patients has to be considered the most significant contributor of decreased mortality observed in our study (8).…”
Section: Discussionmentioning
confidence: 78%
“…Another Brazilian study, Borges et al 6 also found cervical cancer as the most common at the ED, and almost two-thirds of the patients had one of the following primary tumors: urological, breast, gastrointestinal tract and lung cancer. In contrast, most studies found lung cancer as the major driver of visits, followed by breast and colorectal tumors 5 , 7 , 11 , 12 . This inequality is associated with low-resource settings with suboptimal programs such as screening and vaccination 13 .…”
Section: Discussionmentioning
confidence: 87%